Study of a set of reading precursors among Chilean children with Down syndrome - Arango, Paulina S.; Escobar, Jose P.; Orellana, Pelusa; Aparicio, Andrés; Strasser, Katherine; Rosas, Ricardo; Tenorio, Marcela (Frontiers in Psychology, 2023)
Learning to read for children with Down syndrome is relevant because of the impact this ability has on learning and the development of autonomy. Previous research has described reading development in this population, but it is not clear if the process and precursors are the same in a transparent language like Spanish. This study explores performance in a set of precursors (phonological awareness, visual recognition, vocabulary, letter knowledge and verbal reasoning) in 42 children with Down syndrome between 6:0 and 10:11 years. We hypothesized that the participants would have a lower performance than previously reported with children with typical development, particularly in tasks of phonological awareness, because the method for reading instruction in Chile with this population is usually the global method. Our results show that the precursors improve with age, that there are differences in performance between the skills assessed, and the ceiling effect was not observed as would be expected for children with typical development for the abilities assessed at these ages, which suggests that in the children assessed the precursors are not consolidated at these ages. These results suggest that the stimulation of phonological awareness and other reading precursors in children with Down syndrome is important for reading development.